2016
DOI: 10.4283/jmag.2016.21.1.029
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties and Impedance Spectroscopic Studies of Multiferroic Bi1-xNdxFeO3Materials

Abstract: Nd-doped BiFeO 3 materials were synthesized via a sol-gel method. The crystal structure, magnetic properties, and complex impedance spectroscopy of multiferroic Bi 1-x Nd x FeO 3 (BNFO) materials were investigated by Xray diffraction (XRD), Raman scattering, vibrating sample magnetometer (VSM), and complex impedance spectroscopy. Our results show that the lattice crystal constants (a, c) and the ratio c/a of BNFO materials decreased with increasing Nd concentration. All samples exhibited weak ferromagnetism at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The result was responded to the SEM figure. Another factor, the magnetization in BFVO was due to occurring in super exchange interaction between Fe 2+ and Fe 3+ ions [7]. BFVO requires charged compensation with the addition of V 5+ ions, which had been achieved by the transformation of Fe 3+ to Fe 2+ or oxygen vacancies decreased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result was responded to the SEM figure. Another factor, the magnetization in BFVO was due to occurring in super exchange interaction between Fe 2+ and Fe 3+ ions [7]. BFVO requires charged compensation with the addition of V 5+ ions, which had been achieved by the transformation of Fe 3+ to Fe 2+ or oxygen vacancies decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups had reported partial substitution of Fe 3+ with V 5+ ions. Priyanka Godara and Reetu Dahiya et al reported the change of magnetic and dielectric properties with the co-doped with Ba (Sr) and small amount of V. Rietveld refinement studies showed that all samples [7,8]. Benfang Yu et al reported that the electrical properties were improved with the co-doped with La and V [9].…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies showed that RE substitution for Bi-sites created weak ferromagnetic order. That was attributed to partial destruction of spiral spin structure due to structural destruction and RE 3+ -RE 3+ and/or RE 3+ -Fe 3+ super-exchange interactions [14][15][16]. The polarization-electric field hysteresis (P-E) loops of BFO and BYFNO samples measured at room temperature are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%